β-casein gene polymorphism permits identification of bovine milk mixed with bubaline milk in mozzarella cheese - Otaviano, Antonio Roberto [UNESP]; Lima, André Luis F. [UNESP]; Laureano, Monyka M.M. [UNESP]; Sena, Janete A.D. [UNESP]; de Albuquerque, Lúcia G. [UNESP]; Tonhati, Humberto [UNESP] (FapUNIFESP (SciELO), 2008)
Mozzarella cheese is traditionally prepared from bubaline (Bubalus bubalis) milk, but product adulteration occurs mainly by addition of or full substitution by bovine milk. The aim of this study was to show the usefulnes of molecular markers to identify the admixture of bovine milk to bubaline milk during the manufacturing process of mozzarella cheese. Samples of mozzarella cheese were produced by adding seven different concentrations of bovine milk: 0%, 1%, 2%, 5%, 8%, 12% and 100%. DNA extracted from somatic cells found in cheese were submitted to PCR-RFLP analysis of casein genes: α-s1-CN - CSN1S1 that encompasses 954 bp from exon VII to intron IX (AluI and HinfI), β-CN - CSN2 including 495 bp of exon VII (Hae III and HinfI), and κ-CN - CSN3, encompassing 373 bp of exon IV (AluI and HindIII). Our results indicate that Hae III-RFLP of CSN2exon VII can be used as a molecular marker to detect the presence of bovine milk in mozzarella cheese. Copyright © 2008, Sociedade Brasileira de Genética.
Keywords: Casein; Cheese authentication; Gene polymorphism; Mozarella; PCR-RFLP; beta casein; molecular marker; cheese; controlled study; DNA extraction; DNA polymorphism; exon; food analysis; genetic analysis; intron; milk; nonhuman; nucleotide sequence; polymerase chain reaction; restriction fragment length polymorphism; somatic cell; Bovinae; Bubalus; Bubalus bubalis